Study on probiotic as antibiotic replacement to improve egg production in commercial duck farms - Suswoyo, Imam; Ismoyowati, Ismoyowati; Tugiyanti, Elly (Technium BioChemMed, 2021)
Abstract. A research has been conducted to study the potency of probiotics as antibiotic replacements in terms of egg production and income over feed cost at commercial duck farms. The treatments were control, probiotic administration (P1=5 and P2=7 ml/kg feed), and antibiotic administration (A1=0.5 and A2=1 dose). Thus, there were 5 treatment units which were replicated 4 times. Each unit had 30 laying ducks, so in total there were 600 local laying ducks. Parameters observed were egg production as Hen Day Production and egg mass. Hen Day Production was measured by calculating the number of eggs, divided by the number of female ducks in percentage. Egg mass was calculated by the number of eggs multiplied by the weight of the eggs, divided by the number of ducks. The results showed that egg production in control, P1, P2, A1 and A2 was 50.95%, 62.90%, 60.85%, 56.75% and 65.40% respectively. For egg mass, the data were 36.07+3.25; 44.58+3.63; 42.64+4.31; 41.44+3.76; and 45.27+4.57 respectively. Statistical analysis revealed that, for both parameters, there was a significant difference (P<0.05) between control and treatments but not a significant difference among treatment groups. It seemed that probiotics and antibiotics had similar effects on Hen Day Production and egg mass. It can be concluded that probiotics could replace antibiotic administration for laying ducks in terms of egg production.